Intervención fisioterapéutica en paciente de 16 años con pie plano y acortamiento del tendón de Aquiles. - Flores Pacheco, Bryan Eugenio (2023)
The present clinical case is focused on a 16-year-old male patient who presents decreased ankle dorsiflexion capacity and alteration in gait, balance and stability plus flat feet of congenital origin and unspecified obesity. In the interview that was conducted with the mother at the time of the patient's admission, she stated that approximately a month ago her son suffered an Achilles tendon injury. Which led to surgery on the right club foot (Achilles tendon plasty). There were no post-operative complications during the days he was hospitalized for proper monitoring. In his file we can see that his vital signs were normal. However, his anthropometric measurements showed that the patient is overweight at 82kg and a height of 175cm, giving a BMI of 26.8. Therefore, he was advised to improve his eating habits and follow an adequate diet to improve his health and avoid complications such as obesity or chronic non-communicable diseases. After the interview with the patient and family member (mother), it is explained that manual therapy, passive mobilizations, gait re-education exercises on parallel bars, hula hoops, ramp stairs, crumpling the towel with the feet, will be applied. rolling the ball from front to back, lifting the ball with the heels and toe exercises, in order to improve their physical condition through the physiotherapeutic interventions that will be provided to the patient during the week at the Specialized Education Institution " A new sunrise".